Stock Price Analysis in Healthcare Sector Companies On the Indonesia Stock Exchange - Victoria, Ellis Grace; Yuniningsih, Yuniningsih (International Journal of Scientific Research and Management (IJSRM), 2025)
This study analyzes the influence of profitability, liquidity, and solvency on stock prices with dividendpolicy as a mediator variable in healthcare sector companies listed on the Indonesia Stock Exchange for the2020-2023 period. Using a quantitative approach with a comparative causal design, this study involved 9healthcare companies selected through purposive sampling, resulting in 36 observations. Profitability ismeasured using Return on Assets (ROA), liquidity using Cash Ratio, solvency using Equity to Assets Ratio,and dividend policy using Dividend Payout Ratio. Data analysis uses Moderated Regression Analysis (MRA)after meeting the classical assumption test. The results of the study show that profitability has a negativeeffect on stock prices (β=-4,236,647; p=0.026). Liquidity showed a positive but insignificant effect(p=0.075), while solvency had a significant positive effect (p=0.023) on stock valuation. The dividend policyhas been proven to moderate the relationship between profitability and stock price positively (p=0.033), notmoderate the relationship between liquidity and stock price (p=0.119), but to moderate the negativerelationship between solvency and stock price (p=0.017). The research model showed superior predictiveability with an adjusted R-square of 0.750, indicating that 75% of stock price variations could be explainedby the variables in the model. These findings make a theoretical contribution to understanding the dynamicsof the healthcare sector capital market and the strategic implications for management in the formulation ofoptimal financial policies.